Assessing the Influence of AI on Modern Student Writing Standards: An Educators’ Perspective - Alhajji, Reem (Research Journal in Advanced Humanities, 2024)
The study examines the many-sided impact of AI integration in UAE’s education system on student learning and academic outcomes as perceived by teachers. Five key themes emerged through analysis of interview transcripts, which are relevant for this research. According to the results obtained, artificial intelligence has significantly transformed learners’ experiences by providing real-time feedback and personalized assistance. However, potential exists that use of AI may kill people creativity. Respondents also noted a tendency towards uniformity and repetition in students’ writing styles consistent with existing literature. This suggests that there should be an equilibrium between AI-generated content and students’ ideas to preserve scholarly integrity. Additionally, this paper shows that the application of AI tools like ChatGPT has influenced students’ thinking and writing models remarkably indicating excessive reliance on these systems at the expense of deep understanding of issues at hand. What comes out clearly from this investigation is how AI can be strategically managed so as to minimize its demerits yet maximize its benefits in education?